Winter Cover Crops Reduce Spring Emergence and Egg Deposition of Overwintering Navel Orangeworm (Lepidoptera: Pyralidae) in Almonds. Issue 4 (14th July 2022) - Wilson, Houston; Daane, Kent M; Maccaro, Jessica J; Scheibner, Reva S; Britt, Kadie E; Gaudin, Amélie C M
Abstract: Habitat diversification has been shown to positively influence a variety of ecosystem services to agriculture, including biological control of arthropod pests. The impact of increased biodiversity tends to be species specific though, and practices therefore need to be developed on a case-by-case basis for each cropping system. In perennial systems, numerous studies have demonstrated that cover crops can have positive impacts on soil quality and other ecosystem services, such as pollination and pest management. However, few studies have focused on the use of cover crops to enhance pest control in almond orchards, especially winter cover crops. The primary pest of almonds in North America is navel orangeworm, Amyelois transitella Walker, which overwinter as larva or pupa on remnant nuts, many of which remain on the orchard soil surface. In the spring, first flight adults subsequently use these remnant nuts as reproductive substrate. An experiment was conducted to evaluate the influence of two distinct winter cover crop mixtures on overwintering mortality and spring egg deposition of A. transitella . Remnant nuts placed into cover crop plots produced fewer adult A. transitella in the spring, suggesting increased overwintering mortality. Additionally, spring egg deposition was reduced on remnant nuts in the cover crops, possibly due to the ground covers interfering with host location and access. In this way, winter cover crops appear to contribute to the reduction of A. transitella populations in the orchard by altering abiotic and physical conditions, although studies to document specific mechanisms are still needed.